Gangguan Keterlambatan Berbicara (Speech Delay) Pada Anak Usia 6 Tahun Di RA An-Nuur Subang - Qurotul Aini; Putri Alifia (Fakultas Tarbiyah IIQ Jakarta, 2022)
Language is a form of rule or symbol system used by children in communicating and adapting to their environment to exchange ideas, thoughts and emotions. Language can be expressed through speech which refers to verbal symbols. In addition to using verbal symbols, language can also be expressed through writing, gestural signs and music. Language is basically a form of communication between humans. However, from time to time developments take place, these developments are internalized and carried out by intellectual abilities. Children are said to be late in speaking, if at the age their ability to produce sound and communicate is below the average for their age. In essence, speaking is one aspect of a child's development that starts from birth. A child's ability to communicate begins with his reaction to the sound or voice of his father and mother